Numerical simulation of the current-voltage characteristics of the inhomogeneous Schottky diodes - Pincevičius, Albertas; Rakauskas, Rimantas-Jonas (Lietuvos matematikos rinkinys, 2002)
In this paper we offer methods for estimation parameters of diodes of the Schottky by comparing outcomes of calculations and experiment. Definite some parameters of contact area: allocation of a active impurity in this area, to define more precisely a potential barrier in the area, to study tunnel mechanisms of electrons through this potential barrier. Such tasks are important from the practical point of view at improvement of performances of devices. One more problem the procedure helps to decide-to design devices with the established volt-ampere characteristic. In this case we can offer the corresponding allocation of an impurity in contact area, to select a technology for engineering of contact of the Schottky.